Conceptualizing skill mix in nursing and health care: An analysis. (20th September 2018) - Cunningham, Jennifer; O'Toole, Thomas; White, Mark; Wells, John S. G.
Abstract: Aim: This paper aims to unpack the concept of "skill mix" into its constituent parts to achieve a better understanding and reduce confusion associated with the term. Background: Skill mix is a topic that is widely debated and is foremost on the health policy agenda due to specific local pressures within international health services. At present, however, there is large variation in terms of what is understood by the concept of "skill mix" and there is a paucity of research that attempts to analyse this concept. Evaluation: Using Rodgers' evolutionary method of concept analysis, this paper provides an analysis of definitions of skill mix, its attributes and associated terms in the literature. Key issue: Definitions of skill mix are often vague and ambiguous and may refer to one or more attributes of skill mix. Conclusion: A lack of understanding of the concept can lead to an ad hoc interpretation of policy recommendations related to skill mix at local level. Implications for Nursing Management: A better understanding of the concept of "skill mix" and its attributes can assist both policy makers and stakeholders, including nurse management, to ensure that the potential of skill mix is maximized.